(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
this article includes observations on the origin of the “Gooroglu” series of epics, the region of their distribution, the study of epics within the series. In this regard, the variants sung by Uzbek Bakhshis of the “Gooroglu” series of EPICs were made the main object.